The colonization of raccoon (Procyon lotor L. 1758) in Georgia – The beginning of the invasion? - Kalandarishvili, Alexandra; Heltai, Miklós (COLUMELLA – Journal of Agricultural and Environmental Sciences, 2019)
Raccoons have been present in Georgia since the second half of the 20th century. Raccoons were introduced in most parts of the Soviet Union including Azerbaijan from where raccoons eventually found themselves on Georgian territory. Today rural residents are complaining about raccoon damage which is in- duced to their private property, crops, domestic animals and game birds. Regardless of such active damages and frequent sightings of raccoons across Georgia, there are no scientific publications that document the presence of this species in the country. We collected pictures of raccoons that were taken primarily by camera traps set by photographers, researchers and wildlife enthusiasts in Georgia. In additions, the material was retrieved from various sources including social media like Facebook. We conclude that raccoons are not only present in Eastern Georgia but they are spreading towards the central Georgia. We conclude that there are breeding populations of raccoons close to the capital city of Tbilisi as well. According to the local residents, this species is causing tremendous damage both to their property and natural habitats. We thus recommend that in order to protect valuable habitats of Georgia, and resolve hu- man-raccoon conflict monitoring and decreasing of raccoon populations must be set as a priority task of the wildlife conservation is Georgia. We also recommend to conduct further studies on raccoon population sizes which will give clearer picture of the damage degree done to the native species and to private property of local residents.